A kinematic comparison of four abdominal training devices and a traditional abdominal crunch - Sands, W. A.; McNeal, J. R. (The Journal of Strength and Conditioning Research, 2002)
Abdominal exercises are often performed on roller or rocker mechanisms, which have been aggressively promoted through the television and print media. However, justifications are lacking as to why these devices are superior to traditional abdominal exercises such as crunches. This study sought to describe and compare the range of motion (ROM) of several joints during crunches performed on 4 different abdominal conditioning devices (2 roller and 2 pivot types) and a traditional crunch exercise. Ten men (29 ± 5.87 years, 177.5 ± 6.46 cm, 80.96 ± 11.72 kg) and 10 women (33.4 ± 10.16 years, 162.23 ± 3.83 cm, 56.99 ± 7.36 kg) subjects agreed to participate in the study. Subjects were videotaped in the sagittal plane (60 Hz) using standard kinematic methods. Reflective markers were placed on the right temple, auditory meatus, shoulder, hip, knee, ankle, heel, toe, and 2 sternum markers placed on a foam piece strapped to the subject's chest. The videotaped movements were automatically digitized (PEAK5 2-D) and the data smoothed using a Butterworth filter. Relative angular ROMs of the head (temple, auditory meatus, shoulder); neck (auditory meatus, shoulder, hip); trunk (near sternum, shoulder, hip); hip (shoulder, hip, knee); sternum/head (sternum near and sternum far with temple and auditory meatus); sternum/trunk (sternum near and sternum far with shoulder and hip); and a sum of 4 angles (head, neck, trunk, hip) were calculated. Sex by equipment repeated measures analyses of variance (ANOVAs) were calculated on the angles of the 5 exercises. When no main effect for sex was found, the data were collapsed across sex and a one-way ANOVA with repeated measures was calculated on the resulting data. Post hoc analyses of pairwise differences were calculated using Tukey's honestly significant difference statistic. Results showed that crunches performed with the abdominal devices resulted in less ROM in all angles measured when compared with a traditional crunch. The traditional crunch exercise was most closely simulated by the pivot-type devices. The results indicated that prescription of abdominal conditioning exercises via these devices results in training through smaller ROMs compared with a traditional crunch. The specific angle changes may require careful judgment as to appropriate application for exercisers with specific back and neck motion limitations.